Models in active learning in schools - Tulus; Zarlis, Muhammad; Sawaluddin; Syahputra, Muhammad Romi; Marpaung, Tulus Joseph (Talenta Publisher, 2020)
The model is part of a learning structure that has a scope large. Inside there are approaches, strategies, methods, and techniques. One of an important aspect of a learning model is syntax, which is standard steps that must be taken in implementing the model. This syntax should be reflected in the steps of learning in particular detailed in the core learning activities. The results achieved in this activity are the teacher has the ability to develop scenarios or core steps active learning that uses certain learning models through the use of supporting media in teaching and learning activities